2019
DOI: 10.1371/journal.pone.0220823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erosive and abrasive stress on sealing ability of different desensitizers: In-vitro study

Abstract: This in vitro study examined the sealing ability of different desensitizing agents under a chemo-mechanical stress condition. For the study, a total of 144 extracted, caries-free human third molars were used to produce 1 mm-thick dentin discs. The specimens were divided randomly into four groups: Superseal (SS), Gluma (GL), Gluma Self-etch (GS), and Tooth Coat (TC). For each group, the permeability was measured before and after applying the desensitizer, after being exposed to Coca Cola … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Through the coagulation of the plasmatic proteins in the dentinal uid, glutaraldehyde functions as a biological xative, leading to the formation of a precipitate primarily composed of plasma proteins, including albumin. The xation process occurs as the amino groups of dentin collagen intertwine with the two aldehyde groups in glutaraldehyde, forming septa that hinder pulp uid ow within the tubule and thus reduce post operative sensitivity [20]. This precipitate contributes to the partial or complete blockage of dentin tubules.…”
Section: Discussionmentioning
confidence: 99%
“…Through the coagulation of the plasmatic proteins in the dentinal uid, glutaraldehyde functions as a biological xative, leading to the formation of a precipitate primarily composed of plasma proteins, including albumin. The xation process occurs as the amino groups of dentin collagen intertwine with the two aldehyde groups in glutaraldehyde, forming septa that hinder pulp uid ow within the tubule and thus reduce post operative sensitivity [20]. This precipitate contributes to the partial or complete blockage of dentin tubules.…”
Section: Discussionmentioning
confidence: 99%
“…A fluorides-based agent was selected for this study since this fluoride compound in particular was found in several previous studies to provide an optimal dentinal tubule occlusion with reduction of dentin permeability (21) . Fluorides decrease the permeability, possibly by precipitation of insoluble calcium fluoride within the tubules (22) .…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] Although chemical occlusion of dentinal tubules using fluoride, nitrate, and oxalate is common, its effects are not immediate and less efficient in withstanding acid challenges and mechanical stress. 32,46,47…”
Section: Chemical Occlusion Of Dentinal Tubulesmentioning
confidence: 99%